Rolling and Biological Control Products Affect Microdochium Patch Severity on a Sand‐Based Annual Bluegrass Putting Green. (1st November 2018) - Mattox, Clint M.; Kowalewski, Alec R.; McDonald, Brian W.; Lambrinos, John G.; Pscheidt, Jay W.
Abstract : Core Ideas: There is evidence that rolling an annual bluegrass putting green 5 d a wk −1 resulted in a lower severity of Microdochium patch. Two biological control products were shown to significantly lower Microdochium patch severity. Neither biological products nor rolling were shown to completely suppress Microdochium patch; therefore, turfgrass quality was not considered acceptable for any treatments. This study offers evidence of alternative disease control techniques for the management of Microdochium patch on annual bluegrass putting greens. The turfgrass disease Microdochium patch caused by the pathogen Microdochium nivale (Fries) Samuels & I.C. Hallett occurs in cool, humid regions. Fungicide applications are the predominant control method, however increasing pesticide restrictions have generated concern regarding their use. The objective of this research was to evaluate the effects of rolling 5 d wk −1 in combination with three biological control products applied every 2 wk on Microdochium patch severity on an annual bluegrass ( Poa annua L.) putting green in the absence of traditional fungicides. Biological control products included; BW136N ( Trichoderma harzianum Rifai strain T‐22 + Trichoderma virens (J.H. Mill. Giddens & A.A. Foster) Arx strain G‐41), Rhapsody ( Bacillus subtilis strain QST 713), and Provide (a microbial solution containing unspecified strains of Bacillus subtilis, Mucor hiemalis, and Trichoderma harzianum ) + ReVive (7% humic acid derived from Leonardite). Rolling was effective at inhibiting Microdochium patch as measured by area under disease progress curves (AUDPC) in both years on rolled plots compared to not rolled plots by 47 and 75%, respectively. Applications of BW136N and Rhapsody reduced the severity of Microdochium patch as measured by AUDPC compared to the control (66 and 50% reduction, respectively). The ProVide + ReVive combination did not suppress disease in this study. At the peak of disease, turfgrass quality was greatest when rolling was combined with applications of BW136N or Rhapsody. These findings suggest that rolling as well as BW136N or Rhapsody can inhibit Microdochium patch severity and further research into this management method is warranted.